YIELD, ECONOMICS AND QUALITY PARAMETERS OF BABY CORN AS INFLUENCED BY PLANT DENSITIES AND LEVELS OF NITROGEN - M. VENKATA LAKSHM (The Journal of Research ANGRAU, 2016)
Baby corn (Zea mays L.) is grown for vegetable purpose and it is not a separate type of corn. Baby corn can be consumed raw or used as an ingredient in wide variety of dishes in many cuisines across the globe. A field experiment was conducted during kharif, 2014 on sandy loam soils of the Agricultural College Farm, Bapatla. The treatments consisted of four levels of nitrogen in Factor – A (N1 = 60, N2 = 120, N3 = 180 and N4 = 240 kg N ha-1) and four plant densities (P1 : 2,22,222, P2: 1,48,148, P3 : 1,11,111 and P4: 1,66,666 plants ha-1) in Factor – B. Results of the experiment showed that applying 240 kg N ha-1 registered the highest (12024 kg ha-1) cob with husk yield which was statistically comparable (11771 kg ha-1) with 180 kg N ha-1. The highest crude protein in ear (13.8 per cent), crude fibre (33.3 percent) and ash content (14.3 per cent) were registered by 1,11,111 plants ha-1. Crude protein (15.67 per cent), Crude fibre (32.52 per cent) and ash contents (15.67 per cent) increased significantly with increasing levels of nitrogen up to 240 kg ha-1. Benefit cost ratio registered with different treatment combinations indicated 1.2 the lowest with 60 kg N ha-1 along with 2,22,222 plants ha-1 and 3.1 the highest with 240 kg N ha-1 along with 1,66,666 plants ha-1. The treatment with 180 kg N ha-1along with 1,66,666 plants ha-1 too registered 3.1 cost benefit ratio.